Ethics goes to the movies an introduction to moral philosophy - Falzon, Christopher 1957- (New York Routledge, 2019)
Movies hold a mirror up to us, portraying the complexities of human reality through their characters and stories. And they vividly illustrate moral theories that address questions about how we are to live and what sort of people we ought to be. In this book, Christopher Falzon uses movies to provide a rich survey of moral positions as they have emerged through history. These include the ethics of the ancient world, medieval ethics, Enlightenment and Kantian ethics, existentialist ethics and the ethics of the other. Each theory is explained in detail, using a number of examples from the book's wide selection of movies. The discussion draws on a range of recent and not-so-recent films, from Hollywood blockbusters to art-house cinema. In addition to covering thinkers one would expect in an introduction to ethics (e.g., Plato, Aristotle, Kant), the book discusses less canonical figures in detail as well (e.g., Marcuse, Foucault, Habermas). Similarly, the book examines both major ethical theories (e.g., Kantianism, utilitarianism, virtue ethics) and theories too often glossed over in introductory texts (e.g. Stoicism, Epicureanism, Habermas's discourse ethics and Nietzschean ethics). A wide range of movies are discussed, from Hollywood blockbusters and classics like The Dark Knight, Casablanca and Dirty Harry to lesser known films, like Force Majeure and Under the Skin. Atthe end of each chapter a focus on two feature films is included, with a plot summary and interpretations of several key scenes with a time marker indicating when in the film the scenes occur. A Filmography includes all movies discussed in the book and a Glossary covers key philosophical terms and figures.
Prof. Regletto Imbong (Recommending faculty) - Bookfair2019
Includes bibliography, filmography and index.
Keywords: Ethics in motion pictures; Motion pictures -- Moral and ethical aspects; Ethics